2022
DOI: 10.3389/fimmu.2022.911174
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Poor Graft Function Following Hematopoietic Stem Cell Transplantation

Abstract: Poor graft function (PGF) is a life-threatening complication that occurs after transplantation and has a poor prognosis. With the rapid development of haploidentical hematopoietic stem cell transplantation, the pathogenesis of PGF has become an important issue. Studies of the pathogenesis of PGF have resulted in some success in CD34+-selected stem cell boosting. Mesenchymal stem cells, N-acetyl-l-cysteine, and eltrombopag have also been investigated as therapeutic strategies for PGF. However, predicting and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…Our cohort included 10 patients with monolineage severe cytopenia, and therefore was not strictly limited to patients with at least bilineage cytopenia, as suggested to be the definition of PGF by the European Society of Blood and Marrow Transplantation (EBMT) and some other experts or investigators of recent studies ( 2 4 , 8 , 35 , 36 ). However, in our analysis, mono- versus multiple lineage cytopenia did not appear as a factor influencing response to MSC in univariate and multivariate analyses, therefore precluding that this subgroup of patients could have influence the response rate of the overall cohort.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our cohort included 10 patients with monolineage severe cytopenia, and therefore was not strictly limited to patients with at least bilineage cytopenia, as suggested to be the definition of PGF by the European Society of Blood and Marrow Transplantation (EBMT) and some other experts or investigators of recent studies ( 2 4 , 8 , 35 , 36 ). However, in our analysis, mono- versus multiple lineage cytopenia did not appear as a factor influencing response to MSC in univariate and multivariate analyses, therefore precluding that this subgroup of patients could have influence the response rate of the overall cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, PGF is a serious complication after alloHCT and coping with this condition remains a challenge for patients as they may be at increased risk of infections, bleeding events or complications related to iron overload and must undergo an increased number of hospital visits for transfusion support ( 2 , 4 , 5 , 8 ). Currently, there is no consensus on how to manage this condition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying mechanism of PGF still remains unclear and the pathogenesis of PGF is probably multifactorial including immunologic issues as well as abnormalities in stem cells and the bone marrow microenvironment. [18][19][20] Accumulating evidence have shown that increased levels of reactive oxygen species (ROS) might contribute to the occurrence of PGF after allo-HSCT by impairing both HSCs and the BM microenvironment. [19,21,22] The anti-oxidant NAC can overcome the exhaustion of HSCs, improve BM endothelial cells and enhance the engraftment of HSCs by decreasing the cellular ROS levels in patients with PGF.…”
Section: Pathologic Impact Of Iol On Graft Functionmentioning
confidence: 99%